Iron, hepcidin, and the metal connection - Loréal, Olivier; Cavey, Thibault; Bardou-Jacquet, Edouard; Guggenbuhl, Pascal; Ropert, Martine; Brissot, Pierre (Frontiers in Pharmacology, 2014)
Identification of new players in iron metabolism, such as hepcidin, which regulates ferroportin and divalent metal transporter 1 expression, has improved our knowledge of iron metabolism and iron-related diseases. However, from both experimental data and clinical findings, “iron-related proteins” appear to also be involved in the metabolism of other metals, especially divalent cations. Reports have demonstrated that some metals may affect, directly or indirectly, the expression of proteins involved in iron metabolism. Throughout their lives, individuals are exposed to various metals during personal and/or occupational activities. Therefore, better knowledge of the connections between iron and other metals could improve our understanding of iron-related diseases, especially the variability in phenotypic expression, as well as a variety of diseases in which iron metabolism is secondarily affected. Controlling the metabolism of other metals could represent a promising innovative therapeutic approach.